Fusion imaging of pre- and post-procedural computed tomography angiography in transcatheter aortic valve implantation patients: evaluation of prosthesis position and its influence on new conduction disturbances. (13th December 2018) - Ruile, Philipp; Pache, Gregor; Minners, Jan; Hein, Manuel; Neumann, Franz-Josef; Breitbart, Philipp
Abstract: Aims: The purpose of this study was to evaluate prosthesis position by fusion of pre- and post-transcatheter aortic valve implantation (TAVI) computed tomography angiography (CTA) images and to investigate its influence on the occurrence of new conduction disturbances (CD). Methods and results: We performed CTA fusion imaging in 120 TAVI patients (Edwards Sapien 3) on a standard image post-processing workstation to obtain a 3D reconstruction of the transcatheter heart valve (THV) position within the native annulus region. Optimal implantation depth of the THV was defined according to the manufacturers recommendations as 70–80% of the prosthesis above (aortic) and 20–30% below (ventricular) the native annulus plane. Pre- and post-interventional electrocardiograms (ECGs) were assessed for the development of new CD. THV position was found to be within, above, or below the prespecified margins in 32 patients (27%), 71 patients (59%), and 17 patients (14%), respectively. Interobserver reliability was high for fusion measurements [e.g. median THV position 0.983, 95% confidence interval (CI): 0.935–0.996]. Patients with low stent position were significantly more likely to develop new CD compared with patients with optimal or high stent position ( P = 0.039). Independent predictors of CD in multivariate analysis were low THV position [odds ratio (CI): 1.362 (1.093–1.698), P = 0.006] and calcification of the device landing zone [odds ratio (CI): 1.149 (1.024–1.289), P = 0.018]. Conclusion: Fusion imaging of pre- and post-TAVI-CTA allows for the exact evaluation of THV position in relation to the native annulus plane. A low THV position as assessed by fusion imaging is associated with the development of new CD post-TAVI.